Physical activity, and not fat mass is a primary predictor of circadian parameters in young men. (July 2015) - Tranel, Hannah R.; Schroder, Elizabeth A.; England, Jonathan; Black, W. Scott; Bush, Heather; Hughes, Michael E.; Esser, Karyn A.; Clasey, Jody L.
<x xml:space="preserve">Abstract</x> Circadian rhythms are ≈24 h oscillations in physiology and behavior, and disruptions have been shown to have negative effects on health. Wrist skin temperature has been used by several groups as a valid method of assessing circadian rhythms in humans. We tested the hypothesis that circadian temperature amplitude (TempAmp) and stability (TempStab) would significantly differ among groups of healthy young men of varying adiposities, and that we could identify physiological and behavioral measures that were significantly associated with these temperature parameters. Wrist skin temperatures taken at 10 min intervals for 7 consecutive days were determined in 18 optimal (OGroup), 20 fair (FGroup) and 21 poor (PGroup) %Fat grouped young men and subsequently analyzed using available validated software. Body composition, cardiorespiratory fitness, actigraphy, daily nutritional and sleep data, and fasting lipid, insulin and glucose concentration measures were also determined. Significant changes in TempAmp and TempStab parameters in subjects with a single metabolic syndrome (MetS) risk factor compared to those with no MetS factors was observed. In addition, stepwise multivariate regression analyses showed that 50% of the variance in TempAmp was explained by actigraphy (mean steps taken per day; MSTPD), cardiorespiratory fitness, and late night eating per week (#LNE); and 57% in TempStab by MSTPD, time spent in moderate-to-vigorous activity per day, fat mass, and #LNE. Overwhelmingly, physical activity was the most important measure associated with the differences in circadian rhythm parameters. Further research is warranted to determine the effects of increasing the amount and timing of physical activity on the status of the circadian system in a variety of populations.